2007
DOI: 10.1143/jpsj.76.093704
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Properties of Pr-Based Filled Skutterudite PrRu4As12

Abstract: We report on a systematic study of the superconducting characteristics and Pr crystallineelectric-field (CEF) levels of the filled skutterudite PrRu4As12 (Tc = 2.33 K). The temperature dependences of the upper critical field Hc2 and the Ginzburg-Landau (Maki) parameter κ2 suggest s-wave clean-limit superconductivity. The electronic specific heat coefficient γ ∼ 95 mJ/K 2 mol, which is ∼ 1.5 times larger than that of LaRu4As12, indicates 4f -originating quasiparticle mass enhancement. The magnetic susceptibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…[3][4][5][6][7][8] The limited research in this direction may be due to materials difficulties related to the elevated vapor pressure of arsenic. In contrast, crystals of both the phosphides 9 and the antimonides 10 can be grown by low pressure flux techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The limited research in this direction may be due to materials difficulties related to the elevated vapor pressure of arsenic. In contrast, crystals of both the phosphides 9 and the antimonides 10 can be grown by low pressure flux techniques.…”
Section: Introductionmentioning
confidence: 99%
“…µ 0 H c2 (0) value is estimated to be ∼ 9.6 T by the WHH fitting. There appears a possibility of the slight upward deviation in the µ 0 H c2 curve below 2 T, leading to an enhancement in T c by ∼ 10 % in zero field compared with the best-fit WHH curve for µ 0 H c2 (T ) > 2 T. This behavior is also observed in PrRu 4 As 12 13 and PrOs 4 Sb 12 , 24 suggesting that the upward deviation in T c may come from the multiband effect. This multiband effect is also suggested by NQR measurement.…”
mentioning
confidence: 80%
“…[8][9][10][11] On the other hand, PrRu 4 As 12 and PrRu 4 Sb 12 show BCS-type SC properties. 12,13 It is suggested that crystal electric field plays an important role to the heavy ferimon SC properties of PrOs 4 Sb 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The X-ray analysis shows that the samples contain some impurity phase, which is mainly RuAs 2 . The samples are powdered for the NQR measurements.…”
Section: Methodsmentioning
confidence: 99%